Development of Marketing Media for Increasing Interest in Sports Tourism in Kuningan Regency - Deri Muhamad Rojikin; Mugiyo Hartono; Bambang Priyono (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The marketing of sports tourism in Kuningan Regency is less than optimal. This study aims to produce products and test the feasibility of marketing media products based on Instagram social media that are suitable for increasing interest in sports tourism. This research method is a research and development method using 10 research steps according to Sugiyono 2013. Data collection techniques used observation, questionnaires, interviews and documentation. Data analysis techniques are qualitative and quantitative techniques. This research resulted in a product for the development of sports tourism marketing media in Kuningan Regency which is suitable for increasing interest in sports tourism and as an interactive information service medium regarding sports tourism information in Kuningan Regency. Products are made easy with pictures and videos made into content as attractive as possible accompanied by descriptions or related information. The result is that sports tourism development media in Kuningan Regency are suitable for use based on validation by media experts, marketing experts, and tourism experts with decent results and small-scale tests of 30 respondents with good criteria and a large-scale test of 100 respondents with good criteria.